2012
DOI: 10.1016/j.biochi.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional lipids and lipoplexes for improved gene delivery

Abstract: Cationic lipids are the most common non-viral vectors used in gene delivery with a few currently being investigated in clinical trials. However, like most other synthetic vectors, these vectors suffer from low transfection efficiencies. Among the various approaches to address this challenge, functional lipids (i.e., lipids responding to a stimuli) offer a myriad of opportunities for basic studies of nucleic acid–lipid interactions and for in vitro and in vivo delivery of nucleic acid for a specific biological/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 179 publications
(165 reference statements)
1
90
0
4
Order By: Relevance
“…Only a few studies have been published on the interaction of liposomes with prokaryotic cells. 32,33 Our result undoubtedly seems to correlate with these groups and, therefore, a possible mechanism to the fusion process between fluid liposomes and gram-negative bacteria was explained. Due to phosphatidylglycerol (PG) and LPS, liposomes have a negative charge.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Only a few studies have been published on the interaction of liposomes with prokaryotic cells. 32,33 Our result undoubtedly seems to correlate with these groups and, therefore, a possible mechanism to the fusion process between fluid liposomes and gram-negative bacteria was explained. Due to phosphatidylglycerol (PG) and LPS, liposomes have a negative charge.…”
supporting
confidence: 65%
“…[26][27][28][29][30] Liposomes have been successfully used in the delivery of bioactive proteins into flagellated E. coli envelope, 31 and to transfect competent E. coli and Mycoplasma capricolum cells with encapsulated plasmid DNA. 32,33 By using liposomes made of lipid extracts from the whole bacterial membranes of Salmonella minnesota RE595 (the composition and lipids were not identified), Tomlinson et al 33 successfully incorporated phospholipid and proteins into gram-negative bacteria and confirmed that a fusion process was involved in this extensive phospholipid transfer. In this paper, we reported liposome-bacteria fusion with: 1) an artificial liposome of known lipid composition; and 2) intact bacterial cells (both gram-positive and gram-negative).…”
Section: Discussionmentioning
confidence: 99%
“…Many cationic lipids have been employed as synthetic carriers for gene therapy, but only a handful of these compounds have been investigated in clinical trials [13]. Cationic lipids are amphiphilic organic molecules, typically made up of three domains: a cationic head that allows binding to NA; a hydrophobic motif; and a linker separating these two elements [13].…”
Section: Use Of Cationic Lipids In Gene Delivery Systemsmentioning
confidence: 99%
“…However, DNA requires delivery to the nucleus for transcription. Movement of macromolecules through the cytoplasm is greatly restricted due to overcrowding of organelles, the cytoskeleton of the cell and high protein concentrations which slows mobility of the vector and exposes it to the degradative action of endonucleases [91,92]. For successful transfection to occur, the gene delivery vector must protect the cargo and actively traffic the nucleic acid payload towards the nucleus.…”
Section: Nuclear Traffickingmentioning
confidence: 99%